Design of a Dual Polarized Slot Antenna in MLW Technology - Carrasco Paz, Sergio Alejandro (My University, 2024)
In the fifth-generation cellular networks, frequency bands have been allocated in the mmWave regime to take advantage of the large bandwidth at these frequencies. To take full advantage of this bandwidth, spectral efficiency should be increased as much as possible. One of the ways to increase spectral efficiency is by exploiting diversity. Diversity can be created in several ways, for example by using multiple antenna in a MIMO system. Besides this, polarization diversity has been deployed at lower frequencies, however this becomes a challenge at mmWave, since the antenna system needs to be able to radiate two orthogonal polarizations. Together with the half wavelength spacing of a typical MIMO-array the waveguide should support two modes to keep the polarizations sufficiently isolated. Another challenge at mmWave frequencies are the dielectric losses associated with the printed circuit board. To avoid these losses, waveguide antennas can be used which have lower losses. Traditionally, waveguide antennas are difficult to be manufactured since they need galvanic contact between the different layers of the antenna. Gapwavguide technology removes this problem with the use of EBG structures, which can tolerate a gap between the different layers of the mechanical assembly. Moreover, the new MLW technology allows for an even smaller form factor and al lows for smaller structures in its layers, which opens op design space. Therefore, this project aims to create a dual polarized antenna element in MLW technology at 66-71 GHz, (the upper half of the 5G NR n263 frequency band). The antenna element is aimed to support two modes in the same waveguide structure which radiate in two orthogonal polarizations. Furthermore, the antenna shall have a number of radiating slots along the waveguide to investigate the potential impact of grating lobes.